Newspaper Publication to Enhance Writing Skills at the Arabic Language and Salafi Fiqh Department of An-Naqayah Islamic Institute, Latee, Sumenep, Madura - Afandi Afandi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
The implementation of the newspaper publishing process requires to compose 'learning and continuous practice, in order to produce a correct writing according to Arabic rules. At first, the majority of Dalfis students found a difficult to write Arabic, whether it was in the form of information in the Dalfis Arabic newspaper, because there was a lack of learning to write Arabic by Dalfis only once a week. The purposes of the research are as follows: 1. To determine the process of implementation of Arabic newspaper publishing activities in supporting writing skills. 2. To find out the weaknesses in the process of publishing Arabic newspapers in improving writing skills. 3. To find out the factors that influence the publication of Arabic newspapers. The research method, researchers used a descriptive approach by using data collection methods, interview, observation and documentation. Research result In the Arabic language newspaper publishing activities did not run optimally, due to the lack of explanations given by the teacher to the students. The teacher only gives a few titles to students and asked them to write down without giving detailed guidance. Thus it need for good management in Arabic newspaper publishing activities in order it can improve students' skills in writing Arabic. The Weaknesses in activities of publishing Arabic newspapers includes the lack of references related to Arabic such as Arabic magazines, contemporary dictionaries and other one. Thus Dalfis should equip the Arabic language facilities and infrastructure in in order the students are able to read and have a writing skills. The factors influencing the publication of Arabic newspapers are internal factors, namely the lack of explanation given by the teacher about the rules of writing in Arabic, thus the teachers must increase their teaching competence, so that students can understand optimally. Meanwhile, external factors, namely the culture of speaking Arabic among Dalfis students for 24 hours both inside the Dalfis complex and outside.